S7A:5 Sri response, attainment of low disease activity and safety in patients with systemic lupus treated with atacicept in a phase iib study (address ii). (21st March 2018) - Merril, JT; Morand, E; Wallace, DJ; Kao, A; Vazquez-Mateo, C; Chang, P; Fleuranceau-Morel, P; Isenberg, DA
Abstract : Purpose: Atacicept targets B-cell stimulating factors, BLyS and APRIL. ADDRESS II (NCT01972568 ) investigates the efficacy and safety of atacicept in SLE. Methods: In this Phase IIb multicenter study, patients with active (SLEDAI-2K≥6), autoantibody-positive SLE on standard of care therapy received weekly SC injections of atacicept (75 or 150 mg) or placebo (PBO) for 24 weeks. The primary endpoint was proportion of patients achieving SLE responder index (SRI)−4 response at week 24. Other endpoints included SRI-5 through SRI-8 response and low disease activity (LDA) attainment, defined as LDA-1 (SLEDAI-2K≤2), LDA-2 (SLEDAI-2K≤2 and prednisone-equivalent ≤7.5 mg/day), or LLDAS (SLEDAI–2K≤4 without major organ activity, no new disease activity vs previous visit, Physician's Global Assessment≤1, prednisone-equivalent ≤7.5 mg/day, and stable maintenance doses of immunosuppressants). A pre-defined subset of patients was also evaluated, with high disease activity (HDA: SLEDAI-2K≥10 at Screening). Differences in clinical response between patients treated with atacicept and PBO at Week 24 were analysed using odds ratio estimated from logistic regression. Results: The ITT population included 306 patients, and 158 had HDA. There was a trend towards improved SRI-4 response with atacicept vs PBO at Week 24 (p=ns in primary analysis; screening visit as baseline, BL). In a pre-specified sensitivity analysis using study day 1 as BL, a significantly larger proportion of patients on atacicept achieved SRI-4 response at week 24. In the HDA subpopulation, there were significant improvements in SRI-4, –5, −6, –7 and −8 response rates and attainment of LDA with atacicept 150 mg vs PBO (table 1). Atacicept was associated with increased serum C3 and C4, and decreased IgG, IgA, IgM and anti-dsDNA antibodies over time. Rates of treatment emergent adverse event (TEAE) and serious TEAEs were similar among groups. The most frequent serious TEAEs were infections but the incidence was not increased in the atacicept groups vs PBO. Conclusions: Atacicept showed evidence of efficacy in SLE with a dose-dependent reduction of SLE disease activity in patients with HDA. Atacicept was associated with an acceptable safety profile. These results also suggest that more discriminatory endpoints will be useful for future SLE clinical trials.